The Effect of Application of Outdoor Learning Model on Students’ Activeness and Interest in Cultivation Fundamentals Subject - Syamsinar, Syamsinar; Patang, Patang; Hasriani, Hasriani (Journal of Research and Innovation, 2023)
This research is a classroom action research which aims to determine the effect of the application of outdoor learning on students' activeness and interest in learning, as well as to determine the factors that influence students' activeness and interest in learning. The independent variable in this study is the outdoor learning model, while the dependent variable is learning activity and interest. The population in this study was SMKN 4 Bone, while the sample was students of class X ATPH SMKN 4 Bone, totalling 11. The results of this study indicate that outdoor learning has an effect on students' activeness and interest in learning, which can be seen in the results of observations and questionnaires. Factors that influence students' activeness and interest in learning, namely internal aspects and external aspects can be seen on the interview sheet.